2021
DOI: 10.1039/d1sc01654g
|View full text |Cite
|
Sign up to set email alerts
|

Combined spectroscopic studies on post-functionalized Au25 cluster as an ATR-FTIR sensor for cations

Abstract: Using ligand exchange reactions an atomically precise gold cluster was functionalized with a di-thiolated crown ether. Using in situ infrared spectroscopy films of the resulting composite were shown to incorporate metal cations.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
5

Citation Types

0
7
0

Year Published

2021
2021
2023
2023

Publication Types

Select...
5

Relationship

1
4

Authors

Journals

citations
Cited by 6 publications
(7 citation statements)
references
References 56 publications
0
7
0
Order By: Relevance
“…[46][47][48] These molecules find applications in a variety of fields 49,50 from analytical 51 and supramolecular 52 sciences to catalysis, 53 luminescence [54][55][56][57] and photophysics. [58][59][60] Herein, in a new development, we report that the complex formed by ligand 1a (X = O, Fig. 1 and 2) and terbium(III) triflate display strong electronic circular dichroism (ECD) but also CPL properties.…”
Section: Introductionmentioning
confidence: 96%
See 1 more Smart Citation
“…[46][47][48] These molecules find applications in a variety of fields 49,50 from analytical 51 and supramolecular 52 sciences to catalysis, 53 luminescence [54][55][56][57] and photophysics. [58][59][60] Herein, in a new development, we report that the complex formed by ligand 1a (X = O, Fig. 1 and 2) and terbium(III) triflate display strong electronic circular dichroism (ECD) but also CPL properties.…”
Section: Introductionmentioning
confidence: 96%
“…46–48 These molecules find applications in a variety of fields 49,50 from analytical 51 and supramolecular 52 sciences to catalysis, 53 luminescence 54–57 and photophysics. 58–60 Herein, in a new development, we report that the complex formed by ligand 1a (X = O, Fig. 1 and 2) and terbium( iii ) triflate display strong electronic circular dichroism (ECD) but also CPL properties.…”
Section: Introductionmentioning
confidence: 96%
“…Organic ligands on inorganic nanomaterials, such as metal nanoparticles or metal nanoclusters (NCs), play important roles such as in preventing aggregation and tuning interparticle interactions. More crucial roles of organic ligands emerged by decreasing the size of nanomaterials. Protecting ligands of metal NCs with a size of less than 2 nm affects the structures of NCs because of the high specific surface area of NCs. Because the physicochemical properties and reactivities of metal NCs are sensitive to their structures, ligand effects on the structures of metal NCs have been investigated by changing the protecting ligands, mainly through ligand-exchange reactions. In particular, ligand-exchange reactions in atomically precise thiolate-protected gold NCs [denoted Au n (SR) m ] have been investigated because of their variety of physicochemical properties and structures, depending on the thiolate ligands. For example, the optical properties of Au 25 (SR) 18 , one of the most general and stable gold NCs, can be tuned by changing the thiolate ligands because of structural deformation of Au 25 clusters. In addition, ligand-exchange-induced structural transformation has also been scrutinized to obtain mechanistic insights into structural changes. , In these transformations, intermolecular interactions between the protecting ligands on metal NCs are an important factor in regulating the structures of Au n (SR) m . , Therefore, if precise control over ligand-exchange reactivities is achieved for regulating the interactions between protecting ligands, structural perturbation to obtain desired properties would be possible.…”
Section: Introductionmentioning
confidence: 99%
“…Baghdasaryan et al presented a successful ligand exchange between a Au 25 (2-PET) 24 cluster and functionalized thiolated 18-crown-6. 31 According to MALDI-TOF mass analysis, they obtained few exchange species ( x = 5, Au 25 (2PET) 18–2 x ( CE ) x ). ATR-FT-IR studies showed significant red shifts of C–O stretching vibration modes due to the metal ion (e.g., K + , Ba 2+ , and Eu 3+ ) encapsulation into a crown cavity.…”
Section: Introductionmentioning
confidence: 99%
“…Thiolated crown ether (18-crown-6) was previously used as a stabilizing ligand in the synthesis of bigger plasmonic gold nanoparticles where the nanoparticles’ hydrophobicity was modulated by complexation of alkali metals such as sodium and potassium and alkali-earth metal barium. Baghdasaryan et al presented a successful ligand exchange between a Au 25 (2-PET) 24 cluster and functionalized thiolated 18-crown-6 . According to MALDI-TOF mass analysis, they obtained few exchange species ( x = 5, Au 25 (2PET) 18–2 x ( CE ) x ).…”
Section: Introductionmentioning
confidence: 99%